2017
DOI: 10.1111/2041-210x.12897
|View full text |Cite
|
Sign up to set email alerts
|

assignPOP: An r package for population assignment using genetic, non‐genetic, or integrated data in a machine‐learning framework

Abstract: Abstract1. The use of biomarkers (e.g., genetic, microchemical and morphometric characteristics) to discriminate among and assign individuals to a population can benefit species conservation and management by facilitating our ability to understand population structure and demography.2. Tools that can evaluate the reliability of large genomic datasets for population discrimination and assignment, as well as allow their integration with non-genetic markers for the same purpose, are lacking. Our r package, assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
129
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 40 publications
0
129
0
2
Order By: Relevance
“…Likewise, Brophy et al [65] suggested that spawning season and location of Atlantic herring could be predetermined and not learnt from repeated spawning [66]. Support for natal homing and adaptations of Landvik herring to environmental conditions of its marginal habitat also originates from a recent genetic study using 20 microsatellite markers, where Landvikvannet differed from other local herring in Lindåspollene, Lusterfjord and Trondheimsfjord as well as from other herring populations surrounding the Norwegian Sea [67]. Unpublished results on the microsatellite locus Cpa112, which is non-neutral to salinity variability with allele frequencies varying from 45% in the Baltic to 2-4% in the North Sea [27], have shown that Landvik herring is obvious with a frequency of 15% (Carl André, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Brophy et al [65] suggested that spawning season and location of Atlantic herring could be predetermined and not learnt from repeated spawning [66]. Support for natal homing and adaptations of Landvik herring to environmental conditions of its marginal habitat also originates from a recent genetic study using 20 microsatellite markers, where Landvikvannet differed from other local herring in Lindåspollene, Lusterfjord and Trondheimsfjord as well as from other herring populations surrounding the Norwegian Sea [67]. Unpublished results on the microsatellite locus Cpa112, which is non-neutral to salinity variability with allele frequencies varying from 45% in the Baltic to 2-4% in the North Sea [27], have shown that Landvik herring is obvious with a frequency of 15% (Carl André, pers.…”
Section: Discussionmentioning
confidence: 99%
“…This baseline can be further used in combination with machinelearning techniques [67] to assign individuals from mixed fisheries to populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the number of individuals used in stock reassignment training data sets needs to be high (Chen et al. ) and any population variance identified should be tested on an independent data set to avoid overfitting and biased results (Waples ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, delineation may be possible using a combination of environmental markers (e.g., parasites and otolith microchemistry) and molecular markers (MacKenzie and Abaunza ; Chen et al. , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation